Istibdal Wakaf Saham pada Tabung Wakaf Indoesia: Legalitas dan Dampaknya - Muhammad Aiz (JURNAL INDO-ISLAMIKA, 2016)
The grand conclusion of this dissertation is the more contextual the qiyiis the more beneficial it is for the people. In line with that, there is a shift paradigm from